2021
DOI: 10.1111/ane.13448
|View full text |Cite
|
Sign up to set email alerts
|

Supervised exercises versus telerehabilitation. Benefits for persons with multiple sclerosis

Abstract: Objectives The purpose of this study was to investigate the effectiveness of structured telerehabilitation on fatigue, health status, quality of life (QoL), and activities of daily living (ADL) and compare the possible effects with structured supervised exercise programs in patients with Multiple Sclerosis. Materials and methods This study was a randomized, single‐blind trial. Thirty patients with relapsing‐remitting Multiple Sclerosis were included in the study and randomly divided into two groups; structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 40 publications
0
42
0
1
Order By: Relevance
“…Twelve studies were comparator trials, and 20 were single-arm trials. Three single-arm trials were excluded due to the required information not being received via author contact 24–26…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were comparator trials, and 20 were single-arm trials. Three single-arm trials were excluded due to the required information not being received via author contact 24–26…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lack of a control group for comparison, these findings are consistent with previous studies that have demonstrated improvements in walking ability and balance with 12 weeks of homebased and online exercise training in individuals with MS. 29 A systematic review by Perrochon et al 26 found exercise-based gaming interventions at home to be equally effective to conventional therapy. Similarly, Tarakci et al 30 found in-person and telerehabilitation to be equally effective in MS. A study by Jeong et al 31 found that MS-specific physical telerehabilitation produces superior improvements in quality of life as compared with newsletters only. Although prior evidence supports the effectiveness of home-based, 26,32 telehealth, 27,33 or in-person group exercise programs 20 on physical, mental, and social aspects of MS, a combined virtual and group exercise model has not been previously studied.…”
Section: Functional Status Changesmentioning
confidence: 88%
“…Tarakci et al, 2021 compared an in-person rehabilitation program with a telerehabilitation program. After 12 weeks of training, the results were similar in the two groups for fatigue and activity level [52]. Manns et al, 2020 demonstrated a reduction of fatigue after a combined intervention (SitLess and MoveMore) but the difference was not significant compared to usual care [46].…”
Section: Rehabilitationmentioning
confidence: 91%